Audit IT Division In Maintenance Process Internal System PT JAMKRIDA BALI MANDARA With Framework Software Maintenance Maturity Model (SMMM) - Made Dinda Pradnya Pramita; I Made Dhanan Pradipta; Made Sudarma (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
PT Jamkrida Bali Mandara is a credit guarantee institution owned by Bali Province which operates PT Jamkrida Bali Mandara operational company utilizing Management Information System and in developing and maintenace this system company is assisted by some IT staff and vendor. The process of maintenance of existing systems required an assessment of the performance of IT division. This assessment is done through audit method using Maintenance Maturity Model (SMmm) software framework. Based on the results of the audi obtained the highest level of capability is 3.7 in the domain domain maintenance training and the lowest level capability value is 2.03 in domain domain maintenance process / service definition and maintenace process performance Keywords: Software Maintenance Maturity Model, Maintenace System and Capability Level